STriatal-Enriched protein tyrosine Phosphatase (STEP) Regulates the PTPα/Fyn Signaling Pathway - Xu, Jian (J Neurochem, 2015)
The tyrosine kinase Fyn has two regulatory tyrosine residues that when phosphorylated either activate (Tyr(420)) or inhibit (Tyr(531)) Fyn activity. Within the central nervous system, two protein tyrosine phosphatases (PTPs) target these regulatory tyrosines in Fyn. PTPα dephosphorylates Tyr(531) and activates Fyn, while STEP (STriatal-Enriched protein tyrosine Phosphatase) dephosphorylates Tyr(420) and inactivates Fyn. Thus, PTPα and STEP have opposing functions in the regulation of Fyn; however, whether there is cross talk between these two PTPs remains unclear. Here, we used molecular techniques in primary neuronal cultures and in vivo to demonstrate that STEP negatively regulates PTPα by directly dephosphorylating PTPα at its regulatory Tyr(789). Dephosphorylation of Tyr(789) prevents the translocation of PTPα to synaptic membranes, blocking its ability to interact with and activate Fyn. Genetic or pharmacologic reduction of STEP(61) activity increased the phosphorylation of PTPα at Tyr(789), as well as increased translocation of PTPα to synaptic membranes. Activation of PTPα and Fyn and trafficking of GluN2B to synaptic membranes are necessary for ethanol intake behaviors in rodents. We tested the functional significance of STEP(61) in this signaling pathway by ethanol administration to primary cultures as well as in vivo, and demonstrated that the inactivation of STEP(61) by ethanol leads to the activation of PTPα, its translocation to synaptic membranes, and the activation of Fyn. These findings indicate a novel mechanism by which STEP(61) regulates PTPα and suggest that STEP and PTPα coordinate the regulation of Fyn.